Some Observations on the Business School of Tomorrow - Bach, G. L. (Management Science, 1958)
Business school training needs to consider the managerial needs of a quarter century hence. This implies greater emphasis in designing business school curricula and teaching methods on the development of fundamental analytical tools and on the use of these tools in identifying, solving, and implementing decisions on managerial problems. Fundamental analytical tools will come especially from the behavioral sciences, economics, and quantitative methods (including the use of mathematics). The “applied” fields of business (marketing, production, finance, and so on) should, at least now, be viewed primarily as important problem areas where best solutions depend on the effective application of such fundamental tools. This approach implies elimination of much of the current subject matter of business school curricula.